ASUHAN KEBIDANAN PADA IBU NIFAS NY.”R” P4A0H4 DI KLINIK UTAMA LESTARI TEMBILAHAN TAHUN 2019 - Normal Postpartum Midwifery Care; Mia Rita Sari (STIKES HUSADA GEMILANG, 2021)
Nifas is the period that begins after the placenta is born and ends when the uterine organs return to their pre-pregnancy state. In Indonesia, it is estimated that 60% of maternal deaths occur after delivery and 50% within the first 24 hours. Complete postpartum coverage in 2019 in INHIL Regency was 73.5%, while in the main sustainable clinic there were the highest normal postpartum mothers, amounting to 121 people. The purpose of this care is to provide midwifery care for postpartum mothers, Mrs. R P4A0H4 at the Main Lestari Clinic, Tembilahan 2019. The method in this care uses midwifery care management, Varney's line of thought and is documented in SOAP form. The results obtained during 3 visits, there is a gap between theory and practice in the first visit of postpartum given antibiotic therapy that is not in accordance with the needs of patients, In the second postpartum visit did not do nifas gymnastic and mothers who are 35 years old and have 4 children but do not want to use the Long-Term Contraceptive Method In third postpartum visit. The conclusion of this upbringing is that on the first visit to the third visit there is no problem in the provision of care but there is a gap between theory and practice. It is expected that the main sustainable clinic in the future will not provide antibiotic therapy if there is no indication because it can weaken the immune system, providing facilities and infrastructure for gymnastics and patients using the long term contraceptive method.